2012
DOI: 10.1182/blood-2012-06-435875
|View full text |Cite
|
Sign up to set email alerts
|

Methemoglobinemia and ascorbate deficiency in hemoglobin E β thalassemia: metabolic and clinical implications

Abstract: During investigations of the phenotypic diversity of hemoglobin (Hb) E ␤ thalassemia, a patient was encountered with persistently high levels of methemoglobin associated with a left-shift in the oxygen dissociation curve, profound ascorbate deficiency, and clinical features of scurvy; these abnormalities were corrected by treatment with vitamin C. Studies of erythropoietin production before and after treatment suggested that, as in an ascorbate-deficient murine model, the human hypoxia induction factor pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…It has been shown that hemoglobin has an increased susceptibility to undergo oxidation, and when it is subjected to low oxygen tensions, transforming discoid erythrocytes into sickle erythrocytes, increasing the production of MetHb, hemicromos, or products of heme; and causing globin S precipitation in oxidized form of Heinz bodies (13,15,19) . Naoum e Souza (15) , Allen et al (1) and Silva Filho (19) also observed an increase of MetHb in patients with hemoglobinopathies.…”
Section: Discussionmentioning
confidence: 86%
“…It has been shown that hemoglobin has an increased susceptibility to undergo oxidation, and when it is subjected to low oxygen tensions, transforming discoid erythrocytes into sickle erythrocytes, increasing the production of MetHb, hemicromos, or products of heme; and causing globin S precipitation in oxidized form of Heinz bodies (13,15,19) . Naoum e Souza (15) , Allen et al (1) and Silva Filho (19) also observed an increase of MetHb in patients with hemoglobinopathies.…”
Section: Discussionmentioning
confidence: 86%
“…[43][44][45] Additionally, methemoglobin, an endothelial cell activator, is increased in thalassemia 42,46 and may be further increased in Hp2-2 individuals following hemolysis BLOOD, 27 MARCH 2014 x VOLUME 123, NUMBER 13 Hp AND SEVERE MALARIA 2013…”
Section: Discussionmentioning
confidence: 99%
“…Haptoglobin and hemopexin are indicated in this figure as general plasma proteins that (respectively) bind free Hb and heme. Under chronic and large-scale hemolysis, these proteins become limited in their ability to quench these free species that intrinsically are highly reactive and cause oxidative damage when circulating freely in plasma (for recent reviews, see 4,48) Notably, haptoglobin levels are significantly reduced in HbE/b-thal patients (5). To the best of our knowledge, hemopexin levels have not been reported for HbE/b-thal.…”
Section: Introductionmentioning
confidence: 99%